Lifelong Learning as a Strategic Framework for Human Resource Development, Digital Literacy, and Sustainable Education in the Era of Global Transformation - Nurmayani; Sukma Intan Nur’Aini; Okmika Greselly Sembiring; Boby Saputra Hasibuan (PT. Anagata Sembagi Education, 2025)
Lifelong learning is the key to improving human resource quality, adapting to change, and achieving sustainable development. This paper employs a literature study approach, systematically elaborating on schools, lifelong education, and formal, non-formal, and informal learning based on journals and books to understand the framework of lifelong education. Lifelong learning is a comprehensive system encompassing all learning activities that occur throughout human life. The concept aims to create better individuals and societies while serving as a major project in modern communities living in an ever-changing and information-rich world. Lifelong education plays a vital role in helping people continuously adapt to change. Also known as Life Long Education, it emphasizes continuous learning from birth to death through various educational pathways, formal, non-formal, and informal. Thus, lifelong learning underscores that education does not end with formal schooling but continues throughout life across multiple modes of learning.